Infinite point and Riemann–Stieltjes integral conditions for an integro-differential equation - El-Sayed, Ahmed; Gamal, Reda (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we study the existence of solutions for two nonlocal problems of integro-differential equation with nonlocal infinite-point and Riemann–Stieltjes integral boundary conditions. The continuous dependence of the solution will be studied.